Windows Vista Secrets: SP1 Edition - Thurrott Paul (Wiley, 2008)
Get ready to be amazed by numerous tips, tricks, and undocumented features that disclose unique and exciting aspects of the new Windows Vista SP1 operating system. This revised SP1 Edition is packed with over 250 additional pages revealing secrets on topics like configuring Vista, networking, Microsoft Zune, Windows Live OneCare, LIVE, Windows Home Server, and the new and exciting features included in SP1. Leading Windows authority Paul Thurrott reveals hidden Vista abilities and offers a behind-the-scenes look at everything from hardware and software compatibility to security features to keep your data safe. These priceless pieces of little-known expert advice will help you quickly grasp the many benefits of Windows Vista.